Evaluasi Penerapan Rekam Medis Elektronik di Rumah Sakit (Literatur Review) - Monika Monika; Rara Dilla Permatasari; Nadia Salim Bin Usman; Ulhamdiati Ulhamdiati; Edy Susena (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The implementation of Electronic Medical Records (EMR) represents a major advancement in health information systems, playing a vital role in improving service efficiency, data security, and the quality of medical documentation. This study utilizes a literature review approach to assess EMR implementation in hospitals by analyzing findings from 20 relevant journals. Literature sources were obtained from indexed national scientific publications, with a focus on the benefits, challenges, and critical success factors of EMR adoption. The results reveal that EMR use can enhance service efficiency by up to 40%, expedite medical decision-making, and increase the accuracy of patient data. Additionally, EMR reduces the risk of data loss, facilitates coordination among healthcare professionals, and supports more effective integration of medical information. Despite these benefits, EMR implementation encounters several challenges, such as inadequate technological infrastructure, resistance from some healthcare personnel toward digital systems, and the need for ongoing training to ensure optimal use. If not addressed properly, these barriers may limit the system’s effectiveness. Key factors influencing successful implementation include strong management commitment, early involvement of end-users during the planning phase, and system flexibility to meet specific clinical requirements. Therefore, EMR implementation should adopt a holistic approach that integrates human resource readiness, technological capacity, and clear regulatory frameworks. With well-structured strategies, consistent institutional support, and comprehensive training programs, EMR has the potential to be a driving force in the digital transformation of healthcare. This transformation can lead to sustainable improvements in service quality, patient data security, and operational efficiency in hospital settings.